(untitled) (Journal of Pure and Applied Sciences (Science Forum), 2025)
The aim of this study is to examine the subsurface structural disposition and provide useful information on the soil properties with a view to proffer solution and avert future road failure occurrences. A combined scientific approach of remote sensing, geophysical and geotechnical investigations on the earth materials within and around those failed segments have become a fundamental tool to discovering the factors responsible for the insistent problems. Vertical Electrical Soundings (VES) probe of the failed portions gave three (3) to four (4) layered earth interpreted to contain clayey-sand and loose saturated sand units at the upper portion, highly saturated weathered/fractured basement and fresh basement at the lower portion. The resistivity values for the top soil is 139Ωm - 366Ωm, weathered layer is 20Ωm- 101Ωm, weathered/fractured layer is 30Ωm - 473Ωm and fresh basement is 284Ωm - ∞Ωm. The thickness of the top soil is 0.6m - 1.9m, weathered layer is 5.4m to 39.1m, weathered/fractured layer is 2.0m - 25.8m and fresh basement 11.1m - 39.4m respectively. CBR result range from 23.40 – 36.40%, indicating percentage reduction in strength with wetness of 43.7% - 50.8%. Liquid limit, linear shrinkage and plastic limit index gave values in the range of 28.0 - 47.5%, 3.6 - 10.7%, 11.4 - 18.9% respectively. This study implies that integrated structural geology, geophysical and geotechnical investigations offer very useful approach for characterizing near surface earth and thus can help in preparation before engineering structures are found on same.